A method for revising package image colors to express brand perceptions better. Issue 5 (18th June 2019) - Tokutake, Miwa; Kajiyama, Tomoko; Ouchi, Noritomo
Abstract: Product packaging is an important element for branding that directly affects product sales. We have developed a method for creating package images that better express brand perception as a way to motivate purchasing behavior and increase sales. The method works by replacing a color that gives an impression different from the brand perception with one that better expresses the brand perception and that is appropriate for the target product. Brand perceptions perceived by consumers were identified by administering a questionnaire to 160 participants. We constructed two databases: a color database of the correspondence between colors and typical adjectives representing various inner emotional states and a feature database for target products. Using these databases, we applied appropriate colors to packaging (except for areas providing information or containing the logo) to express brand perceptions more accurately. We evaluated this method by performing two experiments, one with 96 participants to determine how changing a package color changed the viewer's impression of the product and the other with seven design experts to determine how this method could help them simulate package design. The results revealed that displaying an appropriately revised package image reduced the gap between the brand perception and the impression obtained upon viewing the package image and gave design experts new ideas for package design.